الرّهن القانوني المؤسّس للبنوك والمؤسسات المالية - بوساحة, نجاة (جامعة الوادي University of Eloued, 2016)
يعتبر الرهن القانوني من أفضل التأمينات العينية لأنه يؤدي وظيفة اقتصادية جد مهمة، لأنها تمنح الدائن الضمان فتشجعه على الإقراض، كما توفر للمدين الائتمان فتمكنه من الحصول على المال لاستثماره. إذن الرهن القانوني له أهمية خاصة في مجال التعامل الائتماني بسبب ما يوفره للدائن من حقي الأفضلية والتتبع، لأنه يمكن البنك أو المؤسسة المالية المقرضة من استرداد مستحقاتهم في حال تقاعس أو عجز العميل المقترض عن الوفاء بالتزامه، و ذلك عن طريق الحجز على العقار المرهون سواء كان المدين لا يزال هو المالك أو انتقلت ملكيته لشخص آخر. Abstract: The legal mortgage is one of the best insurances in kind because it has an important economic function; it confers the creditor security and encourages him to borrow. It also provides the debtor credit to be able to have money for investment. So the legal mortgage has an important role especially in the field of credit transactions because it provides the creditor with the preference and tracking right, and it can enable the bank or the lender financial institution to recover their dues in case of the failure of the borrower or the client’s inability to fulfill his commitment, this will be through the seizure of the mortgaged property, whether the debtor is still the owner or the ownership was transferred to someone else.
Keywords: الرهن القانوني؛ التأمينات العينية؛ البنوك؛ المؤسسات الماليّة؛ المدين؛ الدائن؛ العميل؛ الوفاء؛الحجز على العقار